Geochemical Characteristics of the Jurassic Alkane Gas in the Muli Depression, South Qilian Basin: Implications for Potential of Light Oil and Condensate - Tan, Furong; Li, Yang; Xie, Zhiqing; Bian, Xiaowei; Du, Fangpeng; Liu, Shiming; Lu, Ping; Wang, Jingli (Frontiers in Earth Science, 2022)
The discovery of gas hydrates in the Muli depression has made the South Qilian Basin (SQB) the hotspot for oil and gas exploration. Although many studies have been done on the gas hydrates, the geochemical characteristics have rarely been reported, which can effectively indicate the genetic type, diffusion, biodegradation and thermal maturity of natural gas. In this contribution, molecular composition and carbon isotopes of the alkane gases were collected from gas hydrates and free gases in drilled boreholes of the Mulli Depression. The results show that the majority of the natural gases are oil-type gas with a little coal-type gas. The natural gases have undergone biodegradation, leading to a decrease in the propane content and an increase in the methane content, with a heavier carbon isotope of propane and a lighter carbon isotope of methane. Some of natural gases have experienced diffusion, resulting in a decrease in the methane content and an increasing value of Δ(δ13C1-δ13C2). Furthermore, the wet gases from the natural gases were derived from the cracking of kerogen and crude oil at the thermal maturity stage. The dry gases in small quantities were the production by biodegradation of the wet gases. We propose that potential for light oil and condensate exists in the Jurassic Yaojie Formation. Our new findings on the geochemical characteristics of the natural gases provide new constraints for the study of petroleum systems and deeply buried sediments in the SQB.